Trade in the Mashreq : An Empirical Examination - Blavy, Rodolphe (IMF Working Papers; Working Paper, 2001)
This paper provides a framework for understanding trade patterns in the Mashreq. An augmented gravity model is used to compare actual with expected levels of trade. Trade barriers, political uncertainty, and over-appreciation of domestic currencies seem to explain low levels of international trade. At the intra-regional level, specific trade barriers between Israel and other Mashreq countries reduce further levels of trade. Quite surprisingly, removing Israel from the sample leads to higher actual intra-regional trade than predicted. The analysis suggests that trade liberalization, correction of currency misalignments, reduction of political uncertainty, and improved trade relations with Israel would boost trade in the region.